Whom to represent? National parliamentary representation during the eurozone crisis. Issue 3 (4th March 2018) - Kinski, Lucy
ABSTRACT: The eurozone crisis is commonly associated with a politicization of public debate along national lines. With money being redistributed between member states, national parliamentarians (MPs) seem likely to pit national interests against each other. There is, however, an overlooked second force. Interdependence between eurozone states may lead national MPs and their voters to take into account other European Union citizens. Looking at MPs' parliamentary speeches, this article fills a gap by investigating if and under which conditions individual MPs claim to represent Europeanized constituencies during the crisis. The analysis based on original data from a representative claims analysis of plenary debates on the European Financial Stability Facility (EFSF) in Austria, Germany and Ireland reveals such Europeanized representation. Interestingly, being pro-European does not lead to Europeanized representation. Instead, we witness a 'Eurosceptic Europeanization' in that (left-wing) Eurosceptic MPs voice opposition to the crisis measures, but in the name of European citizens.